A ratiometric fluorescence and colorimetric dual-mode sensing platform based on sulfur quantum dots and carbon quantum dots for selective detection of Cu2 - Zhang, Hanqiang; Li, Yufei; Lu, Haixin; Gan, Feng (Analytical and bioanalytical chemistry, 2022)
A new dual-mode ratiometric fluorescence and colorimetric probe for selective determination of Cu 2+ was developed based on blue-emission sulfur quantum dots (SQDs) and yellow-emission carbon quantum dots (CQDs). The fluorescence and absorbance of CQDs increased in the presence of Cu 2+ due to the Cu 2+ -oxidized o-phenylenediamine group on the surface of the CQDs. Because of the inner filter effect between SQDs and CQDs-Cu 2+ , the fluorescence response of SQDs decreased following the introduction of Cu 2+ . Furthermore, in the presence of Cu 2+ , the dual-mode SQD–CQD probe showed visible color changes under both ultraviolet light and sunlight. Under optimal conditions, the dual-mode probe was used to quantitatively detect Cu 2+ with a linear range of 0.1–5.0 μM for ratiometric fluorescence and colorimetry, with a limit of detection of about 31 nM and 47 nM, respectively. Finally, the dual-mode probe was used for the determination of Cu 2+ in practical samples to expand the practical application, and the difference between ratiometric fluorescence and colorimetric methods was compared. The recovery results confirmed the high accuracy of the dual-mode probe, showing that it has immense potential for sensitive and selective detection of Cu 2+ in practical samples. Graphical abstract